Our experience of surgical treatment of aortic arch obstruction in children in the presence of antegrade selective cerebral perfusion - V. N. Iljinov; Y. V. Yakimova; A. Y. Ivlev; V. O. Kiselev; V. Y. Ginko; Y. V. Krivoshchekov; V. M. Shipulin; A. N. Plekhanov (Acta Biomedica Scientifica)
This work is about outcomes of surgical treatment aortic arch obstruction in children performed with the use of selective cerebral perfusion and moderate hypothermia. The study included 97 patients with aortic coarctation, recoarctation and hypoplastic aortic arch. The patients were divided into 3 groups. 75 patients with isolated coarctation and recoarctation or with concomitant atrial septal defects, patentforamen ovale and patent ductus arterious were assigned to the 1st group. The 2nd group included 13 patients with aortic arch obstruction and ventricular septal defects. The 3rd group consisted of 9 patients with coarctation, recoarctation and complex intracardiac anomalies. All patients underwent reconstruction of the aortic arch with selective cerebral perfusion and moderate hypothermia. Overall mortality rate was 4%. Postoperative complications took place in 7% of the cases: 1% - postoperative bleeding, 1% - paresis of the diaphragm, 2% - pneumothorax, 2% - chylothorax, and 1% of the cases - vocal cords paresis. Respiratory postoperative complications were registered in 5% of cases. In 6% of the cases patients had neurological postoperative complications. After the operation there was no gradientfound between the pressures on upper and lower extremities. We consider that antegrade selective cerebral perfusion and moderate hypothermia during aortic arch reconstruction are effective methods of brain and visceral organs protection.